Reactualisation of Stories of Women's Glory in the Qur'an as a Method of Husband and Wife Relationships in the Family - Alamsyah Alamsyah; M. Nurdin Zuhdi (Journal of Islamic Mubadalah, 2024)
This article examines the stories of the glory of women in the Qur'an, with the method of human stories can take moral messages in it, because the fact is that until now the position of women is not only in the public sphere, in the domestic sphere (family) women still experience a lot of discrimination and injustice, women are often positioned as officers who play a role in the "well, kitchen and bed". Whereas in the Qur'an the position of men and women have the same degree, have the same rights and obligations, have the same glory. The purpose of this article is to analyse the verses about the glory of women as husband and wife relations in the household, then correlated with the actualisation of gender equality in the family. The method used is qualitative, using normative and historical approaches, the type of this article is library research, with data sources from literature on verses about the glory of women in Islam. The results found that the verses about the glory of women in the Qur'an show that Islam came to proclaim women as noble creatures who have dignity, men and women were created from the same element (nafs wahidah). The stories of women's qualifications are relevant to be applied in the household, as a method of husband and wife relations towards a maslahah family